2021
DOI: 10.3390/ijms222413386
|View full text |Cite
|
Sign up to set email alerts
|

Time to Classify Tumours of the Stomach and the Kidneys According to Cell of Origin

Abstract: Malignant tumours are traditionally classified according to their organ of origin and whether they are of epithelial (carcinomas) or mesenchymal (sarcomas) origin. By histological appearance the site of origin may often be confirmed. Using same treatment for tumours from the same organ is rational only when there is no principal heterogeneity between the tumours of that organ. Organ tumour heterogeneity is typical for the lungs with small cell and non-small cell tumours, for the kidneys where clear cell renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Considering the classification of kidney tumours in general, the continuous changes and additions of new types [13,14] indicate a weakness in the system and may suggest that the classifications are not rooted in biology. Our finding of erythropoietin and neuron-specific enolase expression in virtually all ccRCCs may indicate that the EPC is the cell of origin of ccRCC [2,3].…”
Section: Kidney Cancersmentioning
confidence: 70%
See 1 more Smart Citation
“…Considering the classification of kidney tumours in general, the continuous changes and additions of new types [13,14] indicate a weakness in the system and may suggest that the classifications are not rooted in biology. Our finding of erythropoietin and neuron-specific enolase expression in virtually all ccRCCs may indicate that the EPC is the cell of origin of ccRCC [2,3].…”
Section: Kidney Cancersmentioning
confidence: 70%
“…ccRCC may be accompanied by erythrocytosis which has been presumed to be due to production of erythropoietin (EPO) by the erythropoietin-producing cell (EPC) localised in the kidney. Some years ago, we showed that virtually all ccRCC cancer tumour cells expressed erythropoietin as well as the neuroendocrine marker neuronspecific enolase [2], which may suggest that the cell of origin of ccRCC is the EPC [3]. The present review is a follow-up further discussing the cell of origin of ccRCC.…”
Section: Introductionmentioning
confidence: 68%
“…Consequently, the normal cell-of-origin epigenomic profile continues to shape the tumor phenotype through interactions with transforming genetic alterations 4 , 5 . It has been shown that cell-origin based classification of human tumors significantly improves the taxonomy and biological understanding of breast, ovarian, pancreatic, gastric, and kidney cancers, as well as melanoma, retinoblastoma, and lymphoma 6 15 .…”
Section: Introductionmentioning
confidence: 99%